2015
DOI: 10.1186/s12916-015-0347-y
|View full text |Cite
|
Sign up to set email alerts
|

Procalcitonin and pyuria-based algorithm reduces antibiotic use in urinary tract infections: a randomized controlled trial

Abstract: BackgroundUrinary tract infections (UTIs) are common drivers of antibiotic use. The minimal effective duration of antibiotic therapy for UTIs is unknown, but any reduction is important to diminish selection pressure for antibiotic resistance, costs, and drug-related side-effects. The aim of this study was to investigate whether an algorithm based on procalcitonin (PCT) and quantitative pyuria reduces antibiotic exposure.MethodsFrom April 2012 to March 2014, we conducted a factorial design randomized controlled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 38 publications
0
50
0
1
Order By: Relevance
“…All potentially relevant studies cited in documents supplied by the test manufacturers had already been identified by bibliographic database searches. One additional publication was obtained through contact with the authors, 69 after searches had identified the study protocol. 47 Figure 1 shows the flow of studies through the review process, and Appendix 4 provides details, with reasons for exclusions, of all publications excluded at the full paper screening stage.…”
Section: Results Of the Assessment Of Clinical Effectiveness Assessmentmentioning
confidence: 99%
See 4 more Smart Citations
“…All potentially relevant studies cited in documents supplied by the test manufacturers had already been identified by bibliographic database searches. One additional publication was obtained through contact with the authors, 69 after searches had identified the study protocol. 47 Figure 1 shows the flow of studies through the review process, and Appendix 4 provides details, with reasons for exclusions, of all publications excluded at the full paper screening stage.…”
Section: Results Of the Assessment Of Clinical Effectiveness Assessmentmentioning
confidence: 99%
“…Eight studies were conducted in ICU settings 33,37,41,45,50,52,54,61 and all of these studies included only adult participants; we did not identify any studies conducted in paediatric ICU settings that met the inclusion criteria for this review. Ten studies 39,42,44,49,[55][56][57]60,62,69 were conducted in ED settings, of which eight included only adults 42,44,[55][56][57]60,62,69 and two included only children. 39,49 The majority (12 37,39,41,42,44,49,52,57,[60][61][62]69 ) of the included studies measured plasma/serum PCT levels using the BRAHMS PCT Sensitive Kryptor assay (Thermo Fisher Scientific Inc., Waltham, MA, USA).…”
Section: Overview Of Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations